PENGELOLAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DI SEKOLAH DASAR NEGERI KOTA SEMARANG - Ngatini, Ngatini; Ismanto, Bambang (Universitas Kristen Satya Wacana, 2015)
This study aimed to know the management of school academic supervision activity that conducted by principal in the state primary school Pongangan, Gunungpati, Semarang area that included the planning, implementation, and the follow-up to increacse teachersâ performace. This research was conducted with qualitative descriptive method. The collecting data used interview, observation, andÂ documentation. Research results revealed that (1) the planning of academic supervisionÂ by the principal at SDN Pongangan rated very good. (2) the implementation ofÂ academic supervision in SDN Pongangan a great fit the program, the schedule, theÂ instruments that used according to the design, aspects that disupervisi votes hadÂ been lead on target academic supervision adapted to the needs of teachers andÂ schools, the approach was with the program, academic supervision techniques usedÂ varied enough, the academic supervision of implementation constraints by the headÂ of the school is the limited time; (3) the principal efforts made in the follow-up assessed academic supervision has been very good and hard-wired. Activities performed were:Â a) the beginning of each semester were held in groups/joint supervision of teachersÂ meeting school/KKG school; b) performs the inverse to the teacher in order to reflectÂ ourselves; c) implementing guidance on drafting/administration/creation of learning;Â d) emphasize on teachers that always paid attention to the discipline of work inÂ carrying out the task of teaching as a teacher; e) provided guidance for teachers onÂ how to teach in interesting and fun way; f) conducted coaching and guidance forÂ teachers in the use of learning media, techniques/methods of teaching; g) provide aÂ learning device formats that are new to the teacher, and taught how to fill them; g) For School Superintendent gave a complete written report in the end of years.